PENDAMPINGAN PENGELOLAAN DAN PELAPORAN DANA DESA DI DESA SEGUNUNG KECAMATAN DLANGGU KABUPATEN MOJOKERTO - Setyariningsih, Eny; Utami, Budi (Fakultas Ekonomi Universitas Islam Majapahit, 2020)
Changes in management and regulations determined by the government relating to the disbursement of village funds resulted in village officials having to adjust the policy, as a form of need for transparency in financial management. With this policy, the TIM intends to provide assistance to the community, especially the village officials of Segunung, Dlanggu Subdistrict, Mojokerto Regency to help with the existence of a new system and policy so as to tackle the mistakes in village financial management. Some obstacles become obstacles for village officials who are the liding sector of village fund management in conducting management and reporting in accordance with applicable laws. Among them are the limited level of education of human resources, have not done an orderly administration of the use of activity funds. Based on the analysis of the situation, it was found that several obstacles faced by the village officials of Segunung, Dlanggu, Mojokerto, the approach taken was to provide assistance in understanding the laws and regulations as well as management and reporting procedures. The results of the analysis are expected to be a reference in guiding and assisting Segunung village officials. The final result in community service is in the form of a journal of dedication. In carrying out this task, it requires stages that must be passed so that it takes 1 week. Stages of activities carried out are the process of situation analysis and preparation, application and assistance / counseling, material creation, monitoring to produce